Digital Literacy Skills among College Students in Tamil Nadu: A micro-level analysis - Jebaraj, C. Melvin (International Journal of Information Studies, 2026)
Digital literacy has emerged as a foundational competency for academic success, lifelong learning, and employability in contemporary knowledge societies. Beyond basic operational skills, higher education students are increasingly expected to demonstrate competencies in information evaluation, academic research, data handling, online collaboration, and digital ethics. This study investigates the digital literacy skills of college students across three districts of Tamil Nadu Chennai (urban), Tiruchirappalli (semi-urban), and Villupuram (rural) using a structured survey design. Data were collected from 150 undergraduate and postgraduate students using a standardised questionnaire that assessed access to digital devices, usage patterns, competency levels, and awareness of digital safety. Descriptive and inferential statistics were employed for analysis. The findings reveal that while access to smartphones and basic digital tools is widespread, significant disparities persist in advanced digital skills, particularly in research tools, information literacy, data analysis, and cybersecurity awareness. Students from urban institutions consistently outperform their rural counter parts, highlighting a persistent digital divide shaped by infrastructural, institutional, and pedagogical factors. The study underscores the urgent need to integrate digital literacy, faculty capacity building, and targeted interventions to ensure equitable digital skill development in Tamil Nadu’s higher education system.